Enantioselective Alkylation of 2‐Oxindoles Catalyzed by a Bifunctional Phase‐Transfer Catalyst: Synthesis of (−)‐Debromoflustramine B. Issue 18 (7th March 2018) - Craig, Ryan; Sorrentino, Emiliano; Connon, Stephen J.
Abstract: A new bifunctional phase‐transfer catalyst that employs hydrogen bonding as a control element was developed to promote efficient enantioselective SN 2 reactions for the construction all‐carbon quaternary stereocenters in high yield and excellent enantioselectivity (up to 97 %  ee ) utilizing the alkylation of a malleable oxindole substrate. The utility of the methodology was demonstrated through a concise and highly enantioselective synthesis of (−)‐debromoflustramine B. Abstract : A highly enantioselective alkylation of 3‐substituted oxindoles with a broad range of electrophiles was developed using a novel, bulky bifunctional phase transfer catalyst. The methodology was applied to the catalytic asymmetric total synthesis of (−)‐debromoflustramine B.